ANALISIS RETURN ON INVESTMENT (ROI) DAN RESIDUAL INCOME (RI) DENGAN PENDEKATAN DU PONT SYSTEM UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN - Anindya Sukmawardhani; . Suhadak; R. Rustam Hidayat (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
Return On Investment is one of the profitability ratio that measures a company's ability to generate profits with the overall funds available in the company's assets. Residual Income is another alternative that is used to assess the financial performance of the company due to weaknesses in the retun on investment. The use of the two analyzes are expected to complement each other so that the results are better. The results of the analysis that has been done shows that the company's condition fluctuates. Return On Investment that has been analyzed generate a positive value, but with the development of the volatile and are below the cost of capital. These conditions lead to a negative value of Residual Income so that the company could not meet the expected rate of return investors. Companies need to reevaluate their investment policy to produce cost efficient capital so that both positive ROI and RI. Keywords : Return On Investment (ROI), Residual Income (RI), Financial Performance